The Journey to Becoming an English Academic Writing Instructor as a Non-Native English-Speaking Teacher - Al Hariri, Khalid (Journal of the Canadian Association for Curriculum Studies, 2020)
This presentation is an autoethnography that explores my identity as a non-native English-speaking writing instructor. The presentation narrates my feelings, opinions and observations about my educational journey from when I was an undergraduate student in the English department and first introduced to academic writing in English, to becoming a non-native English-speaking teacher (NNEST), until I became an English academic writing instructor. Throughout my years of teaching English to non-native speakers and teaching English academic writing, being foreign to the English language has always had a presence either in the way I identified myself or in the way my society labeled me. Society focused mainly on my non-nativeness to English. However, I was able to self-consciously see my strength of understanding and comparing the writing norms of my first culture with those of the target culture, which was reflected on my teaching in the classroom. Much of the research on NNESTs has focused on issues such as their pronunciation, vocabulary, students’ perceptions, but this study focuses on how I negotiated my identity in teaching writing.